2020
DOI: 10.11113/lspi.v7.16310
|View full text |Cite
|
Sign up to set email alerts
|

Role Play Activities: An Innovative Approach to Teaching Speaking Skills in an ESL Classroom

Abstract: Encouraging students to speak during classroom activities is an effective strategy to improve their acquisition of the target language. Activities related to real life situation such as role play, debate and simulation provide substantial rehearsal and practice and they allow students to not just learn phrases, but also learn how to communicate in various circumstances. Recent studies have revealed that students who are exposed to learning using role play activities improve significantly in speaking competency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…More specifically, all three dimensions of the professional teaching competence, including professional knowledge, designing teaching competence, and implementing teaching competence, had progressed after the intervention. This result corresponds to that of previous research that active learning was beneficial for student teachers as it helped them to understand and develop their professional knowledge (Niiranen et al, 2020;Demirci & Akcaalan, 2020;Ishii, 2017) and improve their teaching competence (Togimin & Jaafar, 2020;Niemi et al, 2016), e.g., developing their teaching materials (Laksana et al, 2019) and implementing and practicing the theories they have learned (Namli AltKaraaslan, 2019).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…More specifically, all three dimensions of the professional teaching competence, including professional knowledge, designing teaching competence, and implementing teaching competence, had progressed after the intervention. This result corresponds to that of previous research that active learning was beneficial for student teachers as it helped them to understand and develop their professional knowledge (Niiranen et al, 2020;Demirci & Akcaalan, 2020;Ishii, 2017) and improve their teaching competence (Togimin & Jaafar, 2020;Niemi et al, 2016), e.g., developing their teaching materials (Laksana et al, 2019) and implementing and practicing the theories they have learned (Namli AltKaraaslan, 2019).…”
Section: Discussionsupporting
confidence: 89%
“…Researchers have found that active learning can effectively stimulate the students' interest, improve their learning engagement and performance, and significantly develop their competence (Cavanagh, 2011;Togimin & Jaafar, 2020;Chen et al, 2020). As a key achievement, the student teachers' professional teaching competency is influenced by active learning strategies, such as autonomous group work, cooperative learning, and problem-solving (Niemi et al, 2016;Virtanen et al, 2017).…”
Section: Active Learningmentioning
confidence: 99%
“…They will be able to communicate ideas as they are put in a situation where they are simulating certain real-life situation or role-playing characters in real life. As mentioned in the findings of study by Togimin and Jaafar (2020), role plays as activities in the classroom trained the students to express themselves and as a result, they managed to speak their sentences smoothly without any interruption from fillers or pausing. Role-playing, according to Kusnierek (2015), is an expressive activity that can offer ample experience and practice to ESL students of probable circumstances or events that they may meet in life.…”
Section: Effectiveness Of Role Play Activity In Improving Students' C...mentioning
confidence: 89%
“…Speaking is a skill that requires the users to keep using the language in order for them to improve the components of the speaking skill. As seen by the research papers analysed, Bhatti (2021); Togimin and Jaafar (2020); Saad and Mansor (2019); Wulandari et al (2019) improvement in regards to speaking skill has been seen as one of the major effectiveness when implementing role play activity in classroom. Fluency, accuracy, accent and pronunciation cannot be learnt through other skills like reading and writing but it can only be acquired if the learners use the language enough to realise and rectify the mistakes that they have done before.…”
Section: Effectiveness Of Role Play Activity In Improving Students' C...mentioning
confidence: 99%
“…Among all, role play activity is the most popular intervention to be used as speaking task. In traditional classroom, 5 studies (Krebt, 2017;Maarof, 2018;Adiantika & Purnomo, 2018;Togimin & Jaafar, 2020;Safitri et al, 2020) set role play as the task for learners to simulate a real life situation. The results from these five studies are positive.…”
Section: Discussionmentioning
confidence: 99%